2009
DOI: 10.1080/00207590903157221
|View full text |Cite
|
Sign up to set email alerts
|

Psychology through international congresses: Differences between regions, countries, and congresses

Abstract: A published database of presentations from the seven most recent International Congresses of Applied Psychology (ICAPs) was compared to a similar but unpublished database (Adair, Anguas-Plata, Unik, & Radons, 2009) on the International Congresses of Psychology (ICPs) for the years 1996-2004. Analyses revealed phenomena characteristic of attendance at both international congresses: Participation rates spike dramatically for host countries; less dramatic regional surges in participation occur when the congress i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Studies of intemational collaboration have shown that the power differential is often uneven; researchers from Western countries are often the dominant party, as they usually have an advantage in terms of language, experience, and resources (Adair et al, 2010). The first is the further development of intemational collaboration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of intemational collaboration have shown that the power differential is often uneven; researchers from Western countries are often the dominant party, as they usually have an advantage in terms of language, experience, and resources (Adair et al, 2010). The first is the further development of intemational collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of such cooperation is a crucial factor in how much a study can contribute to the internationalization of psychology. Studies of international collaboration have shown that the power differential is often uneven; researchers from Western countries are often the dominant party, as they usually have an advantage in terms of language, experience, and resources (Adair et al, 2010). Obviously, the development of a truly international psychology requires the intellectual input of all parties.…”
Section: Discussionmentioning
confidence: 99%
“…Although we based our research on analyses of a database of 34,010 articles from 92 countries in 23 journals, the data reported in this article are largely limited to the publications of the United States and other leading countries identified by their research performance in high-quality primary journals. The remaining data, from countries in the majority world (MW), former Eastern Bloc, and the rest of the world (ROW), focusing on their publications in secondary and international journals and presentations at international congresses, have been reported elsewhere (Adair & Huynh, 2011; Adair, Unik, & Huynh, 2010).…”
mentioning
confidence: 99%
“…A different analysis using data from the Journal of Personality and Social Psychology showed that the number of authors from nations other than the United States has steadily increased since the journal's inception in 1965 and constituted almost one‐third of JPSP articles by 2000 (see Figure ; Quinones‐Vidal, Lopez‐Garcia, Penaranda‐Ortega, & Tortosa‐Gil, ). There has also been an increase in the number of international psychology conferences and the number of countries from which the conference attendees hail (Adair, Coêlho, & Luna, ; Adair, Unik, & Huynh, ; Pawlik & d'Ydewalle, ). Yet another sign of the increasing globalization of psychology is the extent to which cross‐cultural psychology (an important subfield of social psychology) has surged in popularity in recent decades.…”
Section: Real World Impactmentioning
confidence: 99%